The evaluation of prospects for human and saltwater crocodile (Crocodylus porosus) conflict: the case of coastal Bhitarkanika National Park, India - Parida, Satya Narayan; Tripathy, Partha Sarathi; Kumar, Neelesh; Rout, Ajaya Kumar; Panda, Anusuiya; Dobriyal, Manmohan Jagatram; Parida, Pranaya Kumar; Behera, Bijay Kumar (Frontiers in Amphibian and Reptile Science, 2025)
The preservation of biodiversity and managing human-wildlife conflicts are significant problems associated with conservation worldwide. The evaluation of the human-saltwater crocodile (Crocodylus porosus) conflict around the Bhitarkanika National Park revealed an overview of attacks on humans. In this study, it was found that between 2019 and 2025, a total of 28 fatal attacks were reported in the area adjacent to the National Park. It is also highlighted that the past 25 years of government investment policies in C. porosus conservation have led to a significant increase in the number of C. porosus individuals by approximately 36.4 individuals per year over this period of 25 years. The total population follows a moderately complex to highly nonlinear trend. The adult C. porosus follows a moderately nonlinear trend and the sub-adult follows a highly complex trend. The Combined population of both the adults and sub-adults increases by 12.6 individuals per year, revealing significant growth. A key aspect of this study is the difficulty of recovering and conserving large predator populations due to the inherent risk they pose to people and their livelihoods. The findings of the study will aid in creating strategies to reduce the risk of HWC.